G12 Antiepileptic drug medication: are we meeting the information needs of young people?. (12th March 2018) - Ford, G; James, L; Spender-Thomas, K; Capeling, L; Barber, M; Lewis, H
Abstract : Aims: As part of a youth voice challenge day for Takeover, young people (YP) raised concerns that medicine information leaflets are written for parents and not for the YP. The NICE guideline for the diagnosis and management of the epilepsies recommends that YP be given information about medication and side-effects, in formats suited to their needs. improved understanding may be associated with improved concordance and positive health outcomes. A service evaluation was conducted to establish whether the information needs of YP are being met in relation to anti-epileptic drug (AED) treatment. Methods: YP aged 11–16 years within our epilepsy service, who were receiving AED treatment, were surveyed. YP with significant learning disabilities were excluded. A questionnaire was developed to assess their level of understanding, sources of information accessed, information gaps and preferences regarding information formats. YP were asked to evaluate their relevant Medicines for Children leaflet when completing questionnaires in clinic. Results: 23 of 50 eligible YP responded. 6 completed an online survey, 7 completed questionnaires in clinic and 10 returned postal questionnaires. 8 demonstrated good understanding; 8 had gaps in knowledge and 7 poor understanding. 19/23 were able to name their medication. All were able to describe the dosage regime. The majority had vague understanding about how AED treatment works, with some misperceptions. 1/3 had good knowledge of side-effects and managing missed or forgotten doses. The majority received information from doctors (18/23). Half found this information helpful. 9 accessed no other information, 5 accessed websites, 7 leaflets, 3 sourced information from social media. The majority stated they wished to access information on websites and apps. The main information priorities for YP were how to take medication, how to manage missed medication or illness, ability to drive, length of treatment, and how it would affect the YP at school. Current leaflets were described as 'wordy' and unappealing. Conclusion: Information gaps have been identified amongst the YP surveyed. Current leaflets address some but not all of the information needs identified by YP. YP prefer to access information online. In collaboration with Medicines for Children it is hoped that an area of the website will be developed for YP.